(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2013)
The synergistic effect in the antimicrobial activity of the volatile oil blend from Garlic clove (Allium sativum) and tangerine fruits (Citrus reticulata) were investigated and compared to antimicrobial activity when the individual volatile oils were used alone. The volatile oils were extracted by steam distillation using Clevenger hydrodistillator apparatus and each oil was tested for antimicrobial activity, while equal volume of these oils were blended and tested for antimicrobial activity. The microorganisms used include, Staphylococcus aureus isolate, Escherichia coli isolate, Pseudomonas aeruginosa, Salmonella typhi, Candida albicans isolate, Staphylococcus aureus ATCC 25923, Escherichia coli ATCC 25922 and Candida albicans ATCC 90028. The Minimum Inhibitory Concentrations (MICs) ranged from 9.31×10-13 – 7.88 mg/ml for garlic oil, 0.16 – 2.66 mg/ml for tangerine oil and 5.95×10-31 – 1.24 mg/ml for the essential oil blend. Minimum Inhibitory Concentration indicated that the Garlic oil and Tangerine oil blend was better at inhibiting the tested microorganisms than the individual oils except for Escherichia coli ATCC 25922 and Staphylococcus aureus ATCC 25923. The Gas Chromatography-Mass Spectrometry revealed Trisulphide, di-2-propenyl (30.32%) as the major component in the garlic oil extract and 3-Cyclohexene-1-methanol, alpha 4-trimethyl (33.38%) in the tangerine oil. While the equal volume of the oil blend also revealed Trisulphide, di-2-propenyl (15.92%) and 3-Cyclohexene-1-methanol, alpha.4-trimethyl (12.02%) as the major constituents though in lower concentrations. Hence, the more potent antimicrobial properties demonstrated by the oil blend can be exploited further with a view to generate new effective antimicrobial compounds.